The Relationship between Total Bacterial Count and Some Biological Characteristics of Liza aurata caught from Assaid and Annozha port in Lattakia city - العلي, بدر; بدران, معينة; نصور, تيماء (Latakia University Journal -Biological Sciences Series, 2020)
The study was carried out during the summer and winter of 2018 \ 2019 at the Assaid and Annozha port (as polluted site) In order to evaluate the effect of the bacteria on the Liza aurata. Morphometric measurements (length, weight, and sex) as well as the microbiological study to evaluate the heterotrophic bacteria density (in different organs such as intestines, gills and liver) were carried out for 17 individuals. The results showed a significant difference in mean density of bacteria between summer and winter in gills, intestines and liver, where values ​​were in summer higher than in winter for gills (p = 0.001), intestine (p = 0.02) and liver (p = 0.014). It was also observed that the mean value of total bacteria count in the gills was higher than in the intestines and liver where they were p <0.001 and p = 0.001 respectively. In addition, there was a significant difference in the mean value of total bacteria count in gills between males and females, where mean value at females was greater p=0.03, While there was no significant difference in mean values of total bacteria count in the intestine and liver between males and females p = 0.17 and p = 0.36 respectively.